Peran sumber daya manusia dalam mendorong inovasi organisasi - Sari, Rika Yohana; Qadri, Hanif Al; Nellitawati, Nellitawati (Universitas Cokroaminoto Yogyakarta, 2023)
This research aims to investigate the role of Human Resources (HR) in encouraging organizational innovation. The research method used is a literature study that explores various sources and theories related to the role of HR in the context of organizational innovation. The research results show that HR has an important role in driving and facilitating organizational innovation through various aspects, including inspiring and encouraging creativity, facilitating collaboration, managing an organizational culture that supports innovation, providing training and development, supporting the testing and implementation of ideas, and encouraging learning and improvement sustainable. The conclusion of this research is that the role of HR is not only limited to administrative tasks, but also becomes a catalyst in creating a work environment that supports the development of new ideas and implementing innovative solutions in the organization. Therefore, understanding and implementing the effective role of HR can help organizations to remain relevant, competitive and sustainable in facing the ever-changing business environment.